Effects of Chronic Cold Exposure on Proteomics of Lung Tissue in Mice - Li, Moyou; Liu, Ying; Tian, Xiaoye; Wang, Zhuojun; Cheng, Feng; Han, Xiao; Chen, Zheyuan; Ma, Ruihang; Jin, Hongxu (Current Proteomics, 2023)
Background: Cold exposure can induce inflammation-related injury in lung tissue, but the exact mechanism is still unclear.Objective: The study aimed to clarify the proteomic characteristics of lung tissue under cold exposure.Methods: Forty mice were randomly equally divided into a control group and a model group. The model group was exposed to - 20°C for two weeks (4 hours per day), while the control group was maintained at 22 ±2°C. H&E staining and ELISA were used to verify the injury of lung tissue. Furthermore, a quantitative analysis of the overall proteome in the lung of mice exposed to cold stress was conducted by using LC-MS/MS. 15 differentially expressed proteins were selected for PRM validation.Results: According to our results, cold exposure induced lung injury, and the expressions of 151 proteins were upregulated and those of 95 proteins were downregulated. Bioinformatics analysis showed that differentially expressed proteins were associated with tricarboxylic acid cycle, fat metabolism, glycolysis, and oxidative phosphorylation. The expression of gabra2, Klkb1, and complement- related proteins was significantly upregulated. The results of PRM validation were consistent with those of proteomics.Conclusion: We found changes in glycolysis, gabra2, Klkb1, and the complement system in the lung tissue of cold-stressed mice, which may play an important role in cold stress-induced lung injury.
Keywords: Proteome